2016
DOI: 10.1177/0972150916645682
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Choice Overload, Internet Shopping Anxiety, Variety Seeking and Online Shopping Adoption Relationship: Evidence from Online Fashion Stores

Abstract: This study attempts to investigate the nature and impact of choice overload and Internet shopping anxiety on online shopping patronage in the context of fashion products by examining the extent to which consumers seeking variety while shopping online would experience an overload of the innumerable choices offered to them and whether the availability of large assortment of choices will have a significant effect on the patronage of e-stores providing choice in their product offerings. The study also hoped to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 70 publications
0
34
2
1
Order By: Relevance
“…It is shown that website anxiety has a negative effect on a user's intentions to continue using the product or service promoted by the site. For example, online shoppers who begin to feel too anxious do not buy as much [26]. Likewise, those who worry about smartphone use are less likely to continue the service [27].…”
Section: H2: Alternative Attractiveness Positively Influences Negativmentioning
confidence: 99%
“…It is shown that website anxiety has a negative effect on a user's intentions to continue using the product or service promoted by the site. For example, online shoppers who begin to feel too anxious do not buy as much [26]. Likewise, those who worry about smartphone use are less likely to continue the service [27].…”
Section: H2: Alternative Attractiveness Positively Influences Negativmentioning
confidence: 99%
“…Multiple studies have empirically established the direct relationship between 'anxiety' and 'BI' (Adetimirin, 2015;Alenezi, Karim, & Veloo, 2010;Elasmar & Carter, 1996;Tung & Chang, 2008). Nagar and Gandotra (2016) explored this relationship in the context of Internet shopping and established that 'anxiety' has a negative impact on 'patronage intention'. However, Venkatesh et al (2003) found the relationship between 'computer anxiety' and 'BI' to be non-significant.…”
Section: Antecedents To Bimentioning
confidence: 99%
“…System anxiety is the fear that occurs when a person is exposed to the use of information systems [40]- [42], such as computer anxiety, internet anxiety, and online shopping anxiety [43]. Computer anxiety is an anxiety form that reflects the individual transitional tendencies explicitly to be fearful, apprehensive, intimidated, uncomfortable and aggressive when interacting with computer hardware and software [44].…”
Section: B System Anxietymentioning
confidence: 99%
“…It recognized against security threats, cyber fraud, hacker and viruses in an online system. The investigation of internet shopping anxiety in the context of fashion products has attempted by [43], which suggested that variety-seeking behavior is the best predictor of shopping anxiety experienced by online shoppers. Moreover, system anxiety appears as a result of e-commerce transactions and thus can be decreased by a user's experience [70].…”
Section: F Hypotheses Development 1) the Influence Of System Anxietymentioning
confidence: 99%